Students' Cognitive Difficulties in Mastering the Nahwu Rules: A Descriptive Study at SMP IT Al Farabi Bilingual Scool - Siregar, Rahmat Sapaat (Jurnal Cendekia Islam Indonesia, 2025)
This research aims to analyze and describe the cognitive difficulties of students in mastering the nahwu method. This study is a dismissive qualitative research by describing the phenomenon of cognitive difficulties without manipulation and making comparisons in other schools. The data of this study was taken using 3 techniques, namely documentation, questionnaire, and semi-structural interviews. The subjects of this study are junior high school students. The results of the analysis of students' cognitive difficulties in mastering the knowledge of nahwu methods are: (1) difficulty understanding the basic concepts of nahwu, (2) grammatical, (3), weak long-term memory, (4) limited vocabulary, (5) and weak metacognitive strategies, (6) and low transfer of knowledge into a new context The results of the analysis show that the cognitive difficulties are understanding the basic concepts of nahwu/grammatical, weak memory, limitations of vocabulary, weak metacognitive strategies and low transfer of knowledge into new contexts. And there are five main factors that affect these difficulties, namely curriculum, students, learning methods, learning facilities and technology.